Multiple Factors Determine the Oncolytic or Carcinogenic Effects of TLRs Activation in Cancer - Yingxiang Yang; Chengyue Jin; Anthony Yeo; Bo Jin (Journal of Immunology Research)
Toll-like receptors (TLRs) belong to a germline-encoded protein family. These are pattern recognition receptors. They sense pathogen-associated molecular patterns (PAMPs). When this occurs, activation of the NF-ĸB pathway follows. This triggers the innate immune response of the host. The consequent inflammatory cytokine response usually contributes to the elimination of the pathogen. Activation of TLRs also induces an adaptive immune response by a cross-prime mechanism. This mechanism is employed in cancer immunotherapy. Using TLR ligands as adjuvants induces upregulation of costimulatory signals which in turn activates a cytotoxic leukocyte response against cancer cells. However, TLRs are also overexpressed in human cancer cells resulting in increased cell proliferation, migration, invasion, and angiogenesis. An intracellular adaptor, myeloid differentiation factor 88 (MyD88) probably mediates this process. MyD88 is intimately involved with all TLRs except TLR3. One consequence of the interaction between a TLR and MyD88 is activation of NF-ĸB. In this context of a variety of proinflammtory cytokines being produced, chronic inflammation may result. Inflammation is an important protective mechanism. However, chronic inflammation is also involved in carcinogenesis. Activation of NF-ĸB inhibits apoptosis and under certain circumstances, tumor cell survival. In this review, the potential therapeutic value of TLRs in immunotherapy and its role in oncogenesis are explored. The emerging use of artificial intelligence is mentioned.